2022
DOI: 10.3390/plants11223167
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pathogens and Seed Storage in the Dry State

Abstract: Seeds can harbor a wide range of microorganisms, especially fungi, which can cause different sanitary problems. Seed quality and seed longevity may be drastically reduced by fungi that invade seeds before or after harvest. Seed movement can be a pathway for the spread of diseases into new areas. Some seed-associated fungi can also produce mycotoxins that may cause serious negative effects on humans, animals and the seeds themselves. Seed storage is the most efficient and widely used method for conserving plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
5

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 137 publications
1
25
0
5
Order By: Relevance
“…The innermost compartment of the rice seed, milled rice, had a relatively high abundances of those plant-pathogenic fungi, suggesting the possibility of seedborne disease. Seeds may act as carriers of plant-pathogenic fungi that affect growth and productivity of growing plants when environmental conditions and other cultural characteristics are suitable [54,55]. Thus, pathogenic fungi found in the seeds are one of the potential threats to seed quality and crop productivity [56-57].…”
Section: Discussionmentioning
confidence: 99%
“…The innermost compartment of the rice seed, milled rice, had a relatively high abundances of those plant-pathogenic fungi, suggesting the possibility of seedborne disease. Seeds may act as carriers of plant-pathogenic fungi that affect growth and productivity of growing plants when environmental conditions and other cultural characteristics are suitable [54,55]. Thus, pathogenic fungi found in the seeds are one of the potential threats to seed quality and crop productivity [56-57].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi have a number of mechanisms to cope with harsh environmental conditions. For example, their conidia and other specialized structures, such as chlamydospores, allow these fungi to enter a state of dormancy and survive long periods of desiccation 31 . In addition to their physical adaptations, black fungi have also evolved unique metabolic pathways that allow them to survive in extreme environments 20,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant seeds can contain a wide range of microorganisms, which can also be passive carriers of plant diseases. Fungal phytopathogens carried by seeds can significantly reduce seed germination and affect plant yields [19]. A detailed study of the functional potentials of biosurfactants showed that various biosurfactants have antimicrobial and fungicidal properties [20] [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%